2009
DOI: 10.1073/pnas.0900289106
|View full text |Cite
|
Sign up to set email alerts
|

Medial temporal theta state before an event predicts episodic encoding success in humans

Abstract: We report a human electrophysiological brain state that predicts successful memory for events before they occur. Using magnetoencephalographic recordings of brain activity during episodic memory encoding, we show that amplitudes of theta oscillations shortly preceding the onsets of words were higher for laterrecalled than for later-forgotten words. Furthermore, single-trial analyses revealed that recall rate in all 24 participants tested increased as a function of increasing prestimulus theta amplitude. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
231
4
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(284 citation statements)
references
References 38 publications
43
231
4
3
Order By: Relevance
“…This result is consistent with studies in human patients with epilepsy showing positive correlations between prestimulus theta in the MTL and memory (40)(41)(42), and it suggests that theta oscillations are involved in "preparatory" mechanisms that bring the hippocampus into an "online" state (5). Because the monkeys in the current study were not explicitly trained to form a memory of the stimuli, it is unlikely that this preparatory state reflects an overt intention, or motivation, to remember the stimulus.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is consistent with studies in human patients with epilepsy showing positive correlations between prestimulus theta in the MTL and memory (40)(41)(42), and it suggests that theta oscillations are involved in "preparatory" mechanisms that bring the hippocampus into an "online" state (5). Because the monkeys in the current study were not explicitly trained to form a memory of the stimuli, it is unlikely that this preparatory state reflects an overt intention, or motivation, to remember the stimulus.…”
Section: Discussionsupporting
confidence: 90%
“…We next considered whether there was any relationship between modulations in theta-band power and recognition memory performance on the VPLT. In view of previous studies showing positive correlations between prestimulus theta in the human MTL and memory (40)(41)(42), we examined the possibility that the strength of theta-band activity during the baseline period leading up to stimulus onset might predict the strength of memory encoding. We calculated the power in the 3-to 20-Hz range for each LFP during the 800 ms before novel presentations of the 30 stimuli for which the monkey showed the best subsequent recognition memory (high recognition) and before novel presentations of the 30 stimuli for which the monkey showed the worst subsequent recognition memory (low recognition).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, as we confirmed with post hoc analyses, we did not find positive prestimulus SMEs in hippocampal sources. Although other studies ana lyzing the encoding of words have found positive SMEs in prestimulus theta of MTL regions, including hippocampus (Fell et al, 2011;Guderian et al, 2009), it was recently demonstrated that increased prestimulus hippocampal theta activity only predicts subsequent item recognition (Merkow et al, 2014). However, free recall, which depends more on associative encoding as our task, shows a negative SME in post stimulus hippocampal slow theta.…”
Section: Poststimulus Slow Theta Power Decreases Were Not Associated mentioning
confidence: 62%
“…However, other studies have reported negative SMEs in the broad theta band (Burke et al, 2013;Guderian et al, 2009;Long et al, 2014;Sederberg et al, 2007). These theta power decreases are seen during the successful encoding of single items and inter item associations (Greenberg et al, 2015) and are widely detected with surface sensors or iEEG contacts targeting medial temporal lobe (MTL) and fronto temporal structures (Greenberg et al, 2015;Long et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that several aspects of theta activity are involved in the sustained attention to and maintenance of information in working memory (increasing power with increasing memory load) as well as in episodic encoding and retrieval (transient increase of theta power as a consequence of event-related synchronization, mainly in parietal sites) (Klimesch 1999;Klimesch et al 2010). Additionally, an increase in the theta oscillations in temporal regions preceding the presentation of a stimulus predicts its successful encoding (Guderian et al 2009). Therefore, induced responses in both the EEG theta and gamma bands show higher activity when previously observed items are correctly recognized compared with the induced responses when novel items are correctly rejected (old/new effect) during information retrieval periods (Osipova et al 2006).…”
Section: Introductionmentioning
confidence: 99%